(untitled) (American Journal of Islam and Society, 2006)
For first-time students of the increasingly well-researched field of Islamic fundamentalism, or for those with a general interest keen to hone their understanding, Beverly Milton-Edwards’ fourth book, Islamic Fundamentalism Since 1945, is a good place to start. This compact book, running a mere 139 pages of text, has a rather grand ambition: to describe the defining periods in the growth of this phenomenon and introduce the main players as well as the key debates. To a large degree, this ambition is successfully met. Milton-Edwards uses an historical linear approach, and so we begin, in chapter 1, with “a diverse tradition from past to present” that takes us quickly from the events following the Prophet’s death in 632 to the Muslim Brotherhood’s emergence in Egypt in 1928. The author regards its founding father, Hassan al-Banna (1906-49), in “many respects as the founding father of Islamic fundamentalism.” The subsequent chapters examine “The Advance of Secularism”; “Identity and Revivalism”; “Islam Armed”; and “Going Global: Fundamentalism and Terror.” With the penultimate chapter, “Ground Zero and Islamic Fundamentalism,” we are brought to the present. The year 1945, the end of the Second World War, marks the first dismemberment of the imperialist model and the emergence of new nation ...